Childhood Neurodevelopmental Outcome in Low Birth Weight Infants With Post-ligation Cardiac Syndrome After Ductus Arteriosus Closure - Bravo, Maria Carmen; Ybarra, Marta; Madero, Rosario; Pellicer, Adelina (Frontiers in Physiology, 2019)
Background. Post-ligation cardiac syndrome (PLCS) is a common complication of patent ductus arteriosus (PDA) surgical closure in low birth weight infants. It has been associated with mortality, but there is a lack of information about the neurodevelopmental outcome of the survivors. We aimed to explore the prevalence of PLCS and to assess whether this clinical condition is a risk factor for neurodevelopmental impairment. Methods. We retrospectively reviewed the medical charts of all the infants <30 weeks of gestation who underwent ductus arteriosus ligation at our unit between 2005 and 2009. Results. During the study period, 39 preterm infants [mean gestational age 26.4 (2) weeks] underwent surgical closure of the PDA at a mean postnatal age of 25.3 (2.3) days. Twenty six percent of the study population developed PLCS. Five infants died and the follow-up was accomplished in 24 infants (70% of the survivors) at a mean age of 5.3 (1.5) years (range 2-9 years). Neurodevelopmental impairment was observed in 7 infants with PLCS (87%) and in 7 infants without PLCS (44%), OR: 9 (95% CI: 0.9-91.2), p=0.06. Conclusions. Preterm infants undergoing surgical closure of PDA who fulfil the criteria of PLCS according to this study seem to be at higher risk of long-term neurodevelopmental impairment. Prospective clinical trials reporting long-term follow-up data should be designed to confirm this hypothesis.